Configurations of regulatory focus and directing attention and their associations with autonomy, competence, and relatedness need satisfaction/frustration - Hodis F; Hodis G (Taylor and Francis Group on behalf of the Australian Psychological Society, 2024)
Objective The first objective of this research was to investigate the interrelationships of regulatory focus (i.e. promotion and prevention) and the ability to direct attention when studying. The second was to examine whether unobserved groups of individuals having distinct combinations of regulatory focus and directing attention differed on satisfaction/frustration of their basic psychological needs. Method Data were collected from 307 undergraduate students from the US. Latent profile analysis was used to uncover the unobserved groups defined by distinct configurations of promotion, prevention, and directing attention and to examine differences among these groups with regard to satisfaction/frustration of basic needs. Results Three latent groups were identified. Students who had high levels of promotion, prevention, and directing attention, also had strong satisfaction and weak frustration of their psychological needs. Students with low promotion, prevention, and directing attention, also had strong frustration and weak satisfaction of their psychological needs. Conclusions The adaptive pattern of self-regulation, characterized by strong promotion, prevention, and directing attention, was also associated with an adaptive combination of high need satisfaction and low need frustration. A less adaptive pattern of low promotion, prevention, and directing attention was also associated with a maladaptive combination of high need frustration and low need satisfaction.
Keywords: basic psychological need frustration; basic psychological need satisfaction; directive attention; latent profile analysis; prevention; promotion